PRODUKSI DAN KUALITAS HIJAUAN PAKAN PADA LAHAN PASCA TAMBANG DI KABUPATEN KARANGASEM - Suarna, I Wayan; Kusumawati, Ni Nyoman Candraasih; Duarsa, Magna Anuraga Putra (Pastura; Vol 4 No 2DO - 10.24843/Pastura.2015.v04.i02.p05, 2015)
The side-effect of sand mining was disappearing of biomass which caused of land degradation. A study has been carried out to obtain the model legume association with superior grass plants that are adaptive to repair post-mining land on dry land. This research was desgined in association patern between grasses and legumes with manure application, using 8 combination of grasses herbaceous and tree legumse with 3 replications. This research was conducted at Sebudi village, Karangasem district. Panicum maximum var. Trichoglum, Paspalum atratum, Centrocema pubescens, and Clitoria ternatea were used for grasses and legumes respectively. Observed variables were quality and forage production. The results of this research showed that almost all association can be implemented at dryland, and association patern between Panicum and Paspalum with Clitoria gave extra biomass. This association also showed great potential to improve land quality. The quality and production of grasses were greatly influenced by the association of legumes. Panicum and Paspalum associated with both Clitoria or Centrocema gave highest yield. Various of manure showed a non significant difference on quality and production of grass associated with tree legumes, although it tend to increase both of growth and production of grasses.
Keywords: biomass, plant association, land degradation, forage production